Hidden Curriculum dan Problem Lingkungan Pendidikan Islam - Setiawan, Wawan (Tsamratul Fikri | Jurnal Studi Islam, 2020)
Islam education environment is faced with quite serious problem, and the solutions must be sought immediately. The education that given by family environment, madrasah environment, and community environment has not shown significant results. At least it can be seen that a lot of madrasah’s students who still do misconductthat is not accordance with the value of Islam it self. In other hand, they good in academic, but in other condition they have not been able to apply Islamic value in their life. There are still madrasah student who steal, hurt teacher even their parent and other immoral acts. Hidden curriculum so far has not placed it should be, it’s mean the existence of hidden curriculum has not been optimally implemented in Islamic education environment. Islamic educational institution are stiil focused on the ideal curriculum and actual curriculum. Whereas through of hidden curriculum there found moral values, religious and culture that can be instilled the student.